Association between METS-IR and female infertility: a cross-sectional study of NHANES 2013–2018 - Haiyan Li; Hongxia Tan; Zhenbo OuYang; Xianyue Hu; Xianyue Hu; Yanjing Bao; Yanjing Bao; Tianyang Gao; Wenfeng Hua; Wenfeng Hua; Wenfeng Hua (Frontiers in Nutrition, 2025)
BackgroundObesity and metabolic syndrome are significant contributors to infertility in women and are closely associated with insulin resistance (IR). The metabolic score for insulin resistance (METS-IR) is a new, non-insulin-based fasting index used to measure IR. However, the potential of METS-IR as a predictive indicator of female infertility risk has not been established. This study aimed to explore the association between METS-IR and the risk of female infertility.MethodsThis cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018. We conducted multivariate logistic regression, restricted cubic spline (RCS), and threshold effect analyses to investigate the relationship between METS-IR and female infertility.ResultsAccording to the self-reported data, 188 (12.20%) participants were classified as infertile. A significantly higher proportion of participants with elevated METS-IR were found to have infertility. Multivariable logistic regression analysis revealed that METS-IR was significantly associated with increased risk of female infertility, irrespective of the independent variable analysis by continuous variables or tertiles in the fully adjusted model (Model 3, continuous variable: OR = 1.02, 95% confidence interval (CI):1.01–1.04, p = 0.005; tertile 3 vs. tertile 1: OR = 2.00, 95% CI = 1.21–3.28, p = 0.0128, p for trend =0.0126). RCS analysis indicated a linear correlation between METS-IR and the risk of infertility (p = 0.121), and threshold effect analysis further supported this linear association (p = 0.136). Moreover, above the inflection point of 32.94, the risk of infertility significantly increased with increasing METS-IR level (p < 0.0001).ConclusionOur results suggest that high levels of the METS-IR index are positively associated with infertility among reproductive-aged females in the United States.